Ellen Bacon. Interview with Mr. Michael Komichak, the parishioner of the Ukrainian Orthodox Church of the Holy Ascension of Maplewood town, New Jersey, USA - Bacon, Ellen (Young Scholars Grinchenko – Seton International Journal, 2021)
Ellen Bacon. Interview with Mr. Michael Komichak, the parishioner of the Ukrainian Orthodox Church of the Holy Ascension of Maplewood town, New Jersey, USA